2004
DOI: 10.1183/09031936.04.00104803
|View full text |Cite
|
Sign up to set email alerts
|

Airway iron and iron-regulatory cytokines in cystic fibrosis

Abstract: Iron availability is critical to Pseudomonas aeruginosa. The current authors determined sputum iron, ferritin, microalbumin levels and total cell counts (TCC) in 19 adult patients with cystic fibrosis (CF) during an acute exacerbation and repeated analyses following a median of 12 days antibiotic treatment. The current authors also determined sputum interleukin (IL)-1b and tumour necrosis factor (TNF)-a levels because of their putative role in intracellular iron homeostasis. Additional data were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 27 publications
(22 reference statements)
5
92
0
Order By: Relevance
“…The media was modified to include 3 mg ml À 1 ferritin as an alternate iron source to more appropriately reflect the conditions of the CF lung (Stites et al, 1998;Reid et al, 2004;Ghio et al, 2012;Hare et al, 2012). Other modifications included the absence of bovine serum albumin and an increase to 20 mg ml À 1 porcine stomach mucin to better reflect our experience with CF sputum consistency.…”
Section: Inoculation Of Wincf Systemmentioning
confidence: 99%
“…The media was modified to include 3 mg ml À 1 ferritin as an alternate iron source to more appropriately reflect the conditions of the CF lung (Stites et al, 1998;Reid et al, 2004;Ghio et al, 2012;Hare et al, 2012). Other modifications included the absence of bovine serum albumin and an increase to 20 mg ml À 1 porcine stomach mucin to better reflect our experience with CF sputum consistency.…”
Section: Inoculation Of Wincf Systemmentioning
confidence: 99%
“…Just such a scenario may apply during chronic infections in cystic fibrosis lungs, where pyoverdine-negative mutants typically accumulate over time [56][57][58]. One possible explanation for this observation is that siderophores are not required in the lung because iron concentration is increased (7.5 -33 mM; [59,60]). Alternatively, it has been suggested that selection against pyoverdine production occurs because of cheating (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli fur mutant used in these studies can produce more than 100-fold more enterobactin than the parent strain when grown in vitro in iron-replete medium (3), conditions under which Salmonella enterica serovar Typhimurium fur mutants may produce more than 140 M enterobactin (42). Iron is virtually undetectable in respiratory secretions, such as sputum (30,36) or bronchialalveolar lavage (35), and free iron is thought to be as low as 10 Ϫ24 M in the serum (2). In contrast, the cell culture system employed for these studies contains supraphysiologic levels of iron (Յ2 ϫ 10 Ϫ6 M [personal communication from the manufacturer]).…”
Section: Discussionmentioning
confidence: 99%